Program Pengajian Rutin Jum’at sebagai Strategi dalam Meningkatkan Sikap Tawakal para Peserta Didik di MAS Al-Ishlahiyah Binjai - Nasution, Azzara Al-Yari; Hemawati; Salim, Agus (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
The routine Friday recitation program at MAS Al-Islahiyah Binjai as a strategy to improve students' tawakal attitude. The Madrasah stipulates regulations that the program must be followed by students as well as in an effort to motivate them. This study uses descriptive qualitative research to understand the reality of phenomena in the field (research locus) while answering the research objectives regarding the urgency of implementing a routine recitation program to improve religious understanding and noble morals, as well as to improve the advancement of science and improve students' religious understanding. The results of this study indicate that there are significant benefits in participating in the routine Friday recitation program held at MAS Al Islahiyah Binjai school to help students improve their religious attitudes (tawakkal).